Improved mechanical properties of cast Mg alloy welds via texture weakening by differential rotation refill friction stir spot welding. (October 2021) - Fu, Banglong; Shen, Junjun; Suhuddin, Uceu F.H.R.; Chen, Ting; dos Santos, Jorge F.; Klusemann, Benjamin; Rethmeier, Michael
Abstract: Cast magnesium alloys welds produced by refill friction stir spot welding (refill FSSW) show low lap shear strength (LSS) and constantly fail in stirred zone (SZ) shear mode. The cause is most probably related to the heavily textured microstructure. Here, to re-engineer the resulting microstructure, we propose a novel process variant, the differential rotation refill FSSW (DR-refill FSSW). DR-refill FSSW stimulates discontinuous dynamic recrystallization and produces a bimodal microstructure with weakened texture. Therefore, the deformation incompatibility between SZ and thermal-mechanically affected zone is avoided. The welds have 50% higher LSS than that of standard refill FSSW welds, and fail in a different failure mode, i.e., SZ pull-out mode. DR-refill FSSW provides a new and effective strategy for improving the performance of spot welds based on microstructural engineering. Graphical abstract: Image, graphical abstract